PARTICIPATION CITOYENNE DES PYGMEES DES TERRITOIRES DE WAMBA ET DE MAMBASA (RDC). Essai d’une analyse comparative - Jimmy Lingule Kayomba; John Angondo Asaka; Justin Boele Losuna; Salthiel Boyemba Ayomba (IJRDO - Journal of Social Science and Humanities Research, 2019)
Pygmies are increasingly absent from the socio-political and economic space in the Democratic Republic of Congo (DRC). Almost all positions at various levels of power are occupied by the "big blacks". However, it is established that their presence there is earlier than that of all the great blacks. Criticized by a number of analysts, this situation is the result of a series of factors, foremost among which is the lack of involvement in political affairs. Indeed, in the context of democracy, the interest and commitment to the democratic process is the prerequisite for accession to the political sphere and the exercise of power. In these circumstances, it seems to us that we need to evaluate the citizen participation of the Pygmies of the neighboring territories of Wamba and Mambasa recognized as the main sanctuary of these peoples in this country of Central Africa